Sistema de remoção de água de lodo gerado em estação de tratamento de esgoto com duas fases : desaguamento inicial em leito de drenagem seguido de biossecagem - Reis, Renan Felicio dos (2017)
This present research was conducted by whttps://repositorio.ufscar.br/admin/item?itemID=10496ater removal assays related to dewatering and drying of sewage sludge steps. In relation to the first, it was used Drainage Bed (DB) prototype in lab scale (studies of drainage) and in pilot scale (studies of evaporation). It was used anaerobic sludge from UASB reactor, whose dewatering results about studies of drainage, varying three types of geotextile blanket and height of sludge layer, showed that the HaTe® 55/55 UV blanket brought greater drainage capacity, although the analyses results about drained liquid quality was worse in apparent color, turbidity and conductivity when compared to other blankets experienced. In studies of evaporation in DB it was possible to verify and discuss the relation of climate variables with moisture loss, mainly in relation to precipitation, air relative humidity and temperature. Moreover, due to the turning applied, it was observed that, when is made, higher Total Solids (TS) content is obtained in the sludge sample in shorter time than when the turning is not applied. With regard to the drying step, it was conducted biodrying assays, whose methods e results was separated in abroad and Brazil. In the assays conducted abroad (lasting 14 days) it was used mixed sludge (originated from anaerobic, anoxic and aerobic sewage treatment) and wood chips ( 7,1mm) as bulking agent, in proportion of 2:1 (v/v). The results showed that biodrying process promote the removal of bound water (interstitial, surface and intracellular) from sludge and that the turning applying during the biodrying is fundamental to retake biological activity and, thus, increase the temperature again and obtain final sample with higher TS content. At the end, the reactor which resulted in biodried product with higher TS content (reactor Biossecagem II) reached 63,1% of TS, with High Heating Value (HHV) of 17551,9kJ/kgTS, being superior to many parameters found in literature consulted. About the biodrying assays conducted in Brazil (UFSCar), they lasted 20 days and was performed using anaerobic sludge (UASB) previously dewatered in DB, mixed with wood chips (5-15mm) in 5:4 (v/v) proportion, with turning in 6th, 12th, 15th and 18th days. The results also confirmed the occurrence of biological activity, but did not reached themophilic conditions. To this behavior, it was suggested as reason the use of dewatered sludge in natural system (DB) or anaerobic sludge, both situations still not reported in the literature for biodrying process. In the reactor with the best behavior (reactor Biossecagem B) it was obtained final TS content of 47,4%, with HHV of 14661kJ/kgTS and Low Heating Value (LHV) of 14659,9kJ/kgTS. Furthermore, this thesis reports and compiles data from biodrying assays of sewage sludge found in the literature in a synthesis table, as well as discuss and compare the numerous variables and their implications in the process.